Muscle regeneration in gilthead sea bream: Implications of endocrine and local regulatory factors and the crosstalk with bone - Otero-Tarrazón, Aitor; Perelló-Amorós, Miquel; Jorge-Pedraza, Violeta; Moshayedi, Fatemeh; Sánchez-Moya, Albert; García-Pérez, Isabel; Fernández-Borràs, Jaume; García de la serrana, Daniel; Navarro, Isabel; Blasco, Josefina; Capilla, Encarnación; Gutierrez, Joaquin (Frontiers in Endocrinology, 2023)
Fish muscle regeneration is still a poorly known process. In the present study, an injury was done into the left anterior epaxial skeletal muscle of seventy 15 g gilthead sea bream (Sparus aurata) juveniles to evaluate at days 0, 1, 2, 4, 8, 16 and 30 post-wound, the expression of several muscle genes. Moreover, transcripts’ expression in the bone (uninjured tissue) was also analyzed. Histology of the muscle showed the presence of dead tissue the first day after injury and how the damaged fibers were removed and replaced by new muscle fibers by day 16 that kept growing up to day 30. Gene expression results showed in muscle an early upregulation of igf-2 and a downregulation of ghr-1 and igf-1. Proteolytic systems expression increased with capn2 and ctsl peaking at 1 and 2 days post-injury, respectively and mafbx at day 8. Myogenic regulatory factors presented a pattern of expression that fitted well with active myogenesis progression 16 days after the injury, following the recovery of igf-1, pax7, cmet, and cav1 expression; and later on, as well that of cav3, myomaker and myomixer, implicated in the myotube fusion stage. Furthermore, the first days post-injury, the cytokines il-6 and il-15 were also upregulated confirming the tissue inflammation, while tnf was only upregulated at days 16 and 30 to induce satellite cells recruitment; overall suggesting a possible role for these molecules as myokines. The results of the bone transcripts showed an upregulation firstly, of bmp2 and ctsk at days 1 and 2, respectively; then, ogn1 and ocn peaked at day 4 in parallel to mstn2 downregulation, and runx2 and ogn2 increased after 8 days of muscle injury, pointing out a possible tissue crosstalk during the regenerative process. Overall, the present model allows studying the sequential involvement of many regulatory molecules, proposing their role during muscle regeneration, and emphasizing the bone-derived genes that could be sending modulatory signals to the injured muscle to contribute controlling regenerative myogenesis.